Public Administration : A Very Short Introduction - Theodoulou, Stella Z. and Roy, Ravi K. (Oxford, New York Oxford University Press, 2016)
In a modern democratic nation, everyday life is shaped by the decisions of those who manage and administer public policies. This Very Short Introduction provides a practical insight into the development and delivery of the decisions that shape how individuals, and society as a whole, live and interact.
Include Index and Illustration
Keywords: Public administration